Rota crítica de mulheres em situação de violência de gênero em Santa Maria – RS - Arboit, Jaqueline (2019)
This study aimed to analyze the critical path of women in coping with situations of gender-based violence. Qualitative research based on art which settings were the Women’s Police Station, Sexual Violence Reference Team of the University Hospital of Santa Maria, Social Assistance Reference Center, Specialized Social Assistance Reference Center and Shelter House, in the city of Santa Maria, Rio Grande do Sul, Brazil. For the generation of data, individual systematic non-participant observation was used as well as the “talking map” creativity and sensitivity technique coupled with in-depth interviews developed with women in situations of violence. The data analysis was performed through thematic analysis, with the support of the MAXqda software. The study included 12 women whose ages ranged from 21 to 56 years. The driving factors of the critical path of women in coping with situations of violence were related to their knowledge about the specialized police station’s assistance, their perceptions about the experience of different types of violence, the fact that they can no longer stand the violence, concern about their children, as well as the support of their family, of the ex-husband/ex-partner’s relatives and of their female friends. Regarding the response factors related to the availability and quality of services, the positive aspects were the reception and information received at the specialized police station. As negative aspects, the inexistence of a care network, lack of knowledge about other services, lack of privacy and limited hours of assistance at the specialized police station and lack of psychological care to women in the social assistance reference centers stood out. Regarding the response factors related to the social representations of service workers and community considered positive, particular attention is drawn to the understanding of the relevance of organizing a care flow to women in situations of violence. As for the negative representations, the blaming of women and criticism about changes in the Maria da Penha Law stood out. Regarding the response factors related to the positive results obtained, in the police sector the monitoring of women for the removal of belongings from their homes and the removal of the aggressor from the house stood out. Moreover, in the shelter house, the offer to women of the needs for their survival and their children’s and the referral to health services stood out. The negative results draw attention to the unsupportive attitude of the police sector and the lack of support from family members. The decisions executed and actions taken by the women included reporting the aggressor, requesting a restraining order, seeking help from the guardianship council and family members, getting back together with the aggressor and leaving home. The critical path of women in coping with situations of violence begins when they recognize it as unbearable, being driven mainly by the escalation of violence. Their decisions and actions are influenced by the information and welcome received by professionals at the institutional level and the support of friends and family. Investment in human resources qualification and communication between points of the care network will provide positive responses from professionals and services.